Covid-19 Containment Strategies: A Comparative Analysis of Hong Kong and Nepal - Rana, Tika; Chalise, Hom Nath (Journal of Karnali Academy of Health Sciences, 2021)
The new type of corona virus officially named as Severe Acute Respiratory SyndromeCoronavirus 2 (SARS-2 CoV-2) was first reported in Wuhan China in late December 2019. Thisarticle aimed at presenting the preventive strategies implemented against COVID-19 bythegovernment of Nepal and the government of Hong Kong and show how the effective policydiscourses coupled with careful preventive measures play critical roles in controlling the virus.This discussion paper is based on various print and non-print media that cover the informationabout the COVID-19 and the adopted strategies to contain the COVID-19 outbreak in HongKong and Nepal. it appears that efficient political leadership, notwithstanding democraticallyelected or not, people’s health literacy, and effective strategies of the government play key rolesin containing the contagion. Government in jurisdictions like Nepal should invest more resourcesfor development of the skilled manpower and conduct more research studies related to theinfection prevention and control to deal with the emergency outbreak in the future.